ANCAMAN DAN PELUANG KETENAGAKERJAAN DI INDONESIA PADA ERA MASYARAKAT EKONOMI ASEAN (MEA) DALAM PERSPEKTIF HUKUM EKONOMI - Sugiyanto Sugiyanto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
Indonesian workers are one of the most influential components of the economic, political and social fields in the country. The government needs to find a  breakthrough and a brief way to improve the skills and competence of work for Human Resources Indonesia in accordance with the needs of the MEA market and not just a breakthrough that is normative through legislation. The  overnment needs to establish policies to curb foreign workers with visas and work permits and refer to the ASEAN Labor Ministers' Work Program (ALMWP) which regulates labor usage standards, to which Indonesia can also keep illegal workers from entering the Indonesian state . The Government fixes the quality and quantity of labor inspectors to supervise the implementation of Law Number 13 Year 2003 regarding Manpower. The Law on Manpower is expected to be perfected immediately to meet them requirements of juridical, philosophical and sociological enactment